Comparison BEP and R/C of Processed Chicken Products from Local MsMe’s in Kediri - Daroini , Ahsin; Fatmawati, Erlin Widya; Ashifa , Dhewi (CV. Komunitas Dunia Peternakan, 2025)
Poultry agribusiness is a sector that has great opportunities for entrepreneurs, especially because of the increasing public need for animal protein. Fresh poultry products such as carcass meat and eggs need to be further processed to increase added value. MSMEs based on processed poultry products are increasingly developing, especially in the culinary sector which presents food innovations made from chicken such as chicken satay, crispy chicken and dimsum. This research focuses on analyzing the business feasibility of three processed chicken products in MSMEs in the Kediri area. Kediri has the potential to produce broiler chicken meat that meets local needs. The method used in this research is analysis of costs, revenues, profits, BEP (Break Even Point), and R/C Ratio. Costs consist of fixed and variable costs, with total costs calculated using the formula TC = FC + VC. Revenue is calculated based on production quantities and selling prices (TR = P × Q). Profit is obtained from the difference between revenue and total costs (π = TR - TC). BEP is used to determine the break-even point, both in terms of production price and production volume. Meanwhile, the R/C Ratio is used to measure business feasibility, with the R/C criteria > 1 indicating that the business is profitable. This research hoped that MSMEs in Kediri can understand the importance of calculating business feasibility to increase the competitiveness and sustainability of their business in the chicken meat processing industry.